2018
DOI: 10.3390/nu11010004
|View full text |Cite
|
Sign up to set email alerts
|

A Guide to Applying the Sex-Gender Perspective to Nutritional Genomics

Abstract: Precision nutrition aims to make dietary recommendations of a more personalized nature possible, to optimize the prevention or delay of a disease and to improve health. Therefore, the characteristics (including sex) of an individual have to be taken into account as well as a series of omics markers. The results of nutritional genomics studies are crucial to generate the evidence needed so that precision nutrition can be applied. Although sex is one of the fundamental variables for making recommendations, at pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 102 publications
0
33
0
Order By: Relevance
“…It has been reported that PUFA concentrations are higher in females than in males during pregnancy and there are some studies showing sex-specific effects for some PUFA in determining several outcomes [68][69][70][71][72][73][74]140,141]. Although this is still an emerging field, the promotion of research investigating sex-specific differences [142] could provide more information regarding sex-specific effects on gene*sex interactions in determining PUFA levels for a more personalized nutrition. Our genome-wide gene*sex interaction study, has revealed a statistically significant gene*sex interaction involving the DNTTIP2 gene (rs3747965) in determining serum total PUFA (mainly omega-6 PUFA), at the genome-wide level of significance (p < 5 × 10 −8 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that PUFA concentrations are higher in females than in males during pregnancy and there are some studies showing sex-specific effects for some PUFA in determining several outcomes [68][69][70][71][72][73][74]140,141]. Although this is still an emerging field, the promotion of research investigating sex-specific differences [142] could provide more information regarding sex-specific effects on gene*sex interactions in determining PUFA levels for a more personalized nutrition. Our genome-wide gene*sex interaction study, has revealed a statistically significant gene*sex interaction involving the DNTTIP2 gene (rs3747965) in determining serum total PUFA (mainly omega-6 PUFA), at the genome-wide level of significance (p < 5 × 10 −8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although growing evidence exists, most obtained data come from in vitro studies being urgent to perform in vivo studies in animals and human. Individual response to therapeutic diets is striking which appears to have a genetic component [ 16 ]; thus, genetic factors (presence of risk allele) affecting dietary response to antioxidant ingredients of functional meat should be investigated in order to get more targeted and potentially efficient functional meats for the prevention or amelioration of oxidation and their deleterious consequences [ 111 ]. Therefore, the presence of alleles negatively contributing to a lower antioxidant activity of GR, GPx, NO syntase, parooxonase (PON-1) or to a higher prooxidant activity induced by cyclooxygenase, lipoxygenase and different isoforms of cytochrome P450 in some individuals should be investigated by meaning of GWAS and EPIWAS trying to get a GRS (Gene-risk score) that advances the understanding of the reality of nutrigenetics on functional foods addressed to improve antioxidant status [ 112 ].…”
Section: Practical Implications and Future Workmentioning
confidence: 99%
“…Yet, almost simultaneously the premise of personalized medicine[ 10 ] or precision medicine[ 11 , 12 ] has emerged and became more popular, driven by novel and low-cost genetic technologies, rapid advances in computational power, massive, linked databases, and new targeted therapies, in concordance with the rising perception of individualism and patient autonomy. The gender approach in medicine has not been neglected in basic research and applied medicine, but rather it has been (or may be) incorporated into precision medicine approaches[ 13 - 16 ] and translational medicine[ 17 ], or into epidemiological and pathophysiological data as well as into information on treatment options and clinical outcomes[ 18 ]. All these, in turn, may not only shed light on the basis and origin of clinical conditions, but may also shape and dictate actionable guidelines for diagnosis and detection, monitoring, treatment and intervention programs, drug development and administration, and facilitate the design of preventive strategies and health policy, which are all specific to subpopulations with regard to gender (and other factors such as age, risk factors etc .…”
Section: From Evidence For Gender Differences In Health Conditions Tomentioning
confidence: 99%